Phytotoxic activity of compounds from Moutabea guianensis aubl. on Amazonian invasive species - Ripardo Filho, Haroldo da Silva; Pacheco, Luidi Cardoso; Andrade, Edinaldo da Silva; Ribeiro, Williams da Silva; Guilhon, Giselle Maria Skelding Pinheiro; Corrêa, Marivaldo José Costa; Romero, Oscar Augusto Sánchez; Santos, Lourivaldo da Silva; Souza Filho, Antônio Pedro da Silva (Eclética Química, 2016)
This study aimed establish the variations in the phytotoxic activity of hexane, ethyl acetate and methanol extracts of Moutabea guianensis, and methyl caffeate and scopoletin isolated from the ethyl acetate extract, variyng the concentration and the receptor species. Phytotoxic activity bioassays of germination (at 25 °C and 12 hours of photoperiod) and development of radicle and hypocotyl (25 °C and 24 hours of photoperiod) were developed. The seed germination of Mimosa pudica was sensitive to the roots hexane, ethyl acetate and methanol extracts at 1% (w/v), with inhibition potentials in 92%, 100% and 100%, respectively. Comparative analysis on the phytotoxic activity of the tested compounds revealed that scopoletin showed a higher inhibition potential on the seed germination bioassay against Mimosa pudica. Senna obtusifolia was not sensitive to the tested compounds. Methyl caffeate showed the highest potential to inhibit the development of radicle and hypocotyls, and the intensity of the allelopathic effects varied with the concentrations.